Abide in the True Vine (John 15:1-12): Augustine’s Figurative Interpretation, Hermeneutics of Love, and Invitation to Abide in Christ the Mediator - Budhi, Yohanes (JURNAL TEOLOGI REFORMED INDONESIA, 2020)
Studi Agustinian belakangan ini menunjukkan maraknya interes pada tafsir Agustinus atas Injil Yohanes. Namun tak banyak diskusi berkembang terkait dengan inter-relasi antara tafsir figuratif, hermeneutik cinta, dan pengajaran Agustinus tentang Kristus sebagai pengantara. Dalam riset ini, penulis akan menunjukkan relasi antara tafsir figuratif dan hermeneutik cinta Agustinus, berdasarkan tafsirnya atas narasi pokok dan carang-carang anggur. Paper ini akan menganalisis pengajaran sentral Agustinus atas Yohanes 15:1-12 dalam Tractates 80-83 tentang tinggal dalam Kristus sebagai pengantara. Recent Augustinian studies display growing interests in Augustine’s interpretation of the Gospel of John. However, there are few discussions regarding the interrelationship between Augustine’s figurative interpretation, his hermeneutics of love, and his teaching on Christ as the mediator. In this research, I will demonstrate the interrelationship between Augustine’s figurative interpretation and his hermeneutics of love based on his interpretation of the vine and the branches. This paper will analyze the central teaching of the abiding in Christ as mediator in Augustine’s Tractates 80-83 on John 15:1-12.